PENGEMBANGAN MODUL AJAR BERBASIS PjBL TERINTEGRASI KEARIFAN LOKAL UNTUK MENINGKATKAN KREATIVITAS MAHASISWA DALAM MENDESAIN MEDIA PEMBELAJARAN - Sri Hanipah; Fredy; Yonarlianto Tembang; Wa Ode Siti Hamsinah Day (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The availability of systematic teaching modules integrated with local wisdom for the Instructional Media course in the Elementary School Teacher Education Study Program remains limited. As a result, the learning process has not fully supported students' creativity in designing contextual instructional media. This study aimed to develop a project based learning teaching module integrated with local wisdom and to examine its feasibility in enhancing students' creativity in designing instructional media. This study employed a research and development (R&D) approach using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The research participants included 8 students in the small-group trial and 28 students in the large-group trial from the Elementary School Teacher Education (PGSD) Study Program at Musamus University. The data were analyzed using descriptive analysis techniques. The findings revealed that the developed teaching module achieved a mean student response score of 3.52 in the small-group trial, categorized as good, which increased to 3.86 in the large-group trial, also categorized as good.These results indicate that the project based learning teaching module integrated with local wisdom meets the criteria for feasibility as an instructional resource and has the potential to enhance students' creativity in designing contextual and meaningful instructional media. Keywords: Project based learning, local wisdom, teaching module, instructional media, creativity, elementary school teacher education.